Proximate composition and phytochemical analysis of Malaysian Liberica sp. coffee bean and its pulp - Ismail, Nurhuda Syahirah; Zaidan, Uswatun Hasanah; Shamsi, Suhaili; Abd Gani, Siti Salwa; Nillian, Elexson (Universiti Putra Malaysia, 2024)
Arabica, Robusta, and Liberica are the three main coffee species cultivated globally. Liberica coffee is a minor species, accounting for less than 1% of global cultivation. Due to favorable climatic conditions in Malaysia, Liberica coffee dominates coffee production, accounting for 73%, while Robusta makes up the remaining 27%. Nevertheless, the substantial coffee production resulted in approximately 15 million tons of discarded skin and pulp, contributing to environmental pollution. This study was conducted due to insufficient information and research on the proximate composition and phytochemical compounds of the coffee bean and pulp from Liberica sp. This study aims to determine the proximate composition of coffee beans and pulp extracts from Liberica sp. and to identify the phytochemical composition using liquid chromatography-mass spectrometry (LC-MS) analysis. The nutritional values of carbohydrates, protein, crude fiber, crude fat, and ash were obtained using proximate analysis. Coffee beans exhibited the highest value for crude protein (11.96%) and crude fiber (11.83%), whereas coffee pulp has the highest significant value for moisture content (68.81%) and ash (7.31%). LC-MS analysis shows emmotin A and deoxymiroestrol were the major phytochemical compounds. These findings contribute to understanding the nutritional value and phytochemical compounds of coffee beans and pulp from Liberica sp. that may contribute to sustainable waste management and other applications in the food and beverage industry.